Facile preparation and thermal performances of hexadecanol/crosslinked polystyrene core/shell nanocapsules as phase change material. Issue 11 (15th January 2014) - Li, Hairong; Jiang, Ming; Li, Qi; Li, Denian; Huang, Jing; Hu, Waping; Dong, Lijie; Xie, Haian; Xiong, Chuanxi
<x xml:space="preserve">Abstract</x> In this study, we report the synthesis of nanoencapsulated phase change material (PCM) with hexadecanol as core and crosslinked polystyrene (PS) as shell material via facile one‐pot emulsion polymerization and its thermal performances. By this method, no high shear homogenization is required to create nanocapsules in emulsion polymerization. The nanosized core/shell structure of the hexadecanol/PS capsules was confirmed by scanning electron microscopy and transmission electron microscope. Thermal performances of the nanoencapsulated PCM were determined using differential scanning calorimetry and thermogravimetry. The results indicated that the hexadecanol/PS nanocapsules had relatively high latent heat of fusion and good thermal stability, which make them attractive for thermal energy storage and heat transfer applications. POLYM. COMPOS., 35:2154–2158, 2014. © 2014 Society of Plastics Engineers